Static bandwidth allocation on optical networks - Mahadevan, V.; Yu, W.; Zhou, J. (2009)
A detailed understanding of the many facets of the Internet's topological structure is critical for evaluating the performance of networking protocols, for assessing the effectiveness of proposed techniques to protect the network from nefarious intrusions and attacks, or for developing improved designs for resource provisioning. In this way Available bandwidth estimation is a vital component of admission control for quality-of-service (QoS) on Internet in the world. In coming years, Optical networks are come to dominate the access network space. Ethernet passive optical networks, which influence the all of subscriber locations of Ethernet, seems bound for success in the optical access network. In this Review Paper we first prepare an introduction to Ethernet passive optical networks structure, then related to our totally categorize the bandwidth allocation methods to three groups as Static and Router-Based and Windows-Based, we will explain seven major weaknesses on static group and describe the improvements on them one by one. Finally in this survey, we found some roles and principles in static bandwidth allocation methods which explain them separately. We hope in the next article we will explain the Dynamic bandwidth allocation weaknesses and improvements then make a comparison between static and dynamic bandwidth allocations. Following that, at the end, we will propose an algorithm on dynamic bandwidth allocation and evaluate it.